Sex-specific differences and risk factors for 30-day mortality in acute pulmonary embolism – results from the Serbian University Multicenter Pulmonary Embolism registry - Matijašević, Jovan; Mirić, Milica; Vučićević Trobok, Jadranka; Peković, Sandra; Andrijević, Ilija; Džudović, Boris; Subotić, Bojana; Obradović, Slobodan (Vojnosanitetski pregled, 2022)
Background/Aim. The prediction role of gender in early mortality in patients with acute pulmonary embolism (PE) is still debatable. The aim of the study was to examine sex-specific factors in all-cause 30-day mortality in patients suffering from acute PE. Methods. Acute PE subjects (n = 532), 49.6% men, were derived from a “real-life” observational multicenter study. We assessed independent risk factors as predictors for early (one-month) fatal outcome in men, women and total population using univariate Cox regression analysis. Results. Age, obesity, hypertension, renal dysfunction, anemia, community-acquired pneumonia, and smoking history presented statistically significant sex-specific differences. One-month mortality was 13.7%, without significant difference in survival based on sex (Log Rank test; p = 0.324). Tachycardia at admission [hazard ratio (HR) = 2.61, p = 0.004], coronary artery disease (HR = 2.30, p = 0.047), immobilization four weeks prior to a PE episode (HR = 2.31, p = 0.018) and older age (HR = 1.03, p = 0.017) in women, while chronic obstructive pulmonary disease (COPD) (HR = 4.03, p
Keywords: age factors; coronary disease; immobilization; mortality; pulmonary disease, chronic obstructive; pulmonary embolism; risk factors; sex factors; tachycardia